Maintenance olaparib plus bevacizumab in patients with newly diagnosed advanced high-grade ovarian cancer: Main analysis of second progression-free survival in the phase III PAOLA-1/ENGOT-ov25 trial. (October 2022) - González-Martín, Antonio; Desauw, Christophe; Heitz, Florian; Cropet, Claire; Gargiulo, Piera; Berger, Regina; Ochi, Hiroyuki; Vergote, Ignace; Colombo, Nicoletta; Mirza, Mansoor R.; Tazi, Youssef; Canzler, Ulrich; et al.
Abstract: Background: PAOLA-1/ENGOT-ov25 (NCT02477644) demonstrated a significant progression-free survival (PFS) benefit with maintenance olaparib plus bevacizumab versus placebo plus bevacizumab in newly diagnosed, advanced ovarian cancer. We report the prespecified main second progression-free survival (PFS2) analysis for PAOLA-1. Methods: This randomised, double-blind, phase III trial was conducted in 11 countries. Eligible patients had newly diagnosed, advanced, high-grade ovarian cancer and were in response after first-line platinum-based chemotherapy plus bevacizumab. Patients were randomised 2:1 to olaparib (300 mg twice daily) or placebo for up to 24 months; all patients received bevacizumab (15 mg/kg every 3 weeks) for up to 15 months. Primary PFS end-point was reported previously. Time from randomisation to second disease progression or death was a key secondary end-point included in the hierarchical-testing procedure. Results: After a median follow-up of 35.5 months and 36.5 months, respectively, median PFS2 was 36.5 months (olaparib plus bevacizumab) and 32.6 months (placebo plus bevacizumab), hazard ratio 0.78; 95% confidence interval (CI) 0.64–0.95; P = 0.0125. Median time to second subsequent therapy or death was 38.2 months (olaparib plus bevacizumab) and 31.5 months (placebo plus bevacizumab), hazard ratio 0.78; 95% CI 0.64–0.95; P = 0.0115. Seventy-two (27%) patients in the placebo plus bevacizumab group received a poly(ADP-ribose) polymerase inhibitor as first subsequent therapy. No new safety signals were observed for olaparib plus bevacizumab. Conclusion: In newly diagnosed, advanced ovarian cancer, maintenance olaparib plus bevacizumab provided continued benefit beyond first progression, with a significant PFS2 improvement and a time to second subsequent therapy or death delay versus placebo plus bevacizumab. Graphical abstract: Image 1 Highlights: We report the main second progression-free survival analysis of PAOLA-1. Median second progression-free survival was significantly longer with olaparib + bevacizumab (bev) versus bev alone. Addition of maintenance olaparib to bev provided benefit beyond first progression. No new safety signals for olaparib were identified with longer follow-up.